Diagnostic and prognostic role of renal histopathology in rheumatic diseases - F. Saccon; M. Gatto; M. Larosa; F. Ometto; M. Felicetti; R. Padoan; M. Zen (PAGEPress Publications, 2018)
The objective was to evaluate renal involvement in several rheumatic diseases (i.e. rheumatoid arthritis, systemic lupus erythematosus, Sjögren syndrome, systemic sclerosis, systemic vasculitides). The method chosen was to define histopathological profiles reported in renal biopsies performed on patients with renal involvement due to different rheumatic diseases. Renal involvement observed in patients with rheumatic disease can be the direct result of the disease per se and/or a complication of drugs used in the disease treatment. The clinical-pathological correlations derived from the study of renal tissues can be useful for differential diagnosis, prognosis assessment and therapeutic decisions. Renal biopsy should be considered as an important tool for the management of nephropathies in patients with systemic rheumatic diseases.